Evaluation of Oxidative Stress and some Biochemical Parameters in Normal Pregnant Women - Kakey, Musher I.; Abdoulrahman, Kamaran K.; Uthman, Gulbahar R. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
Pregnancy is associated with many metabolic changes in normal pregnant woman, this leads to change in physiological, biochemical, and hematological parameters drastically. The test subjects were selected among those attending to Maternity Teaching Hospital in Erbil Governorate between March 2017 and August 2017. Four groups of individuals were included in this study, 230 pregnant women divided into three groups (Group 1 first trimester, Group 2 second trimester, and Group 3 third trimester) and Group 4 contained 90 nonpregnant women as control. Full automatic chemical analyzer (Cobas C311, Germany) was used to determine the biochemical parameters. The EL ×800 Absorbance Microplate Reader from BioTek (USA) instruments is used to measure the activity of superoxide dismutase (SOD), catalase (CAT), and malondialdehyde (MDA) in serum. The results of this study showed a significant increase in serum albumin, glucose, total bilirubin, direct bilirubin, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, creatinine, urea, cholesterol, low-density lipoprotein, and MDA in pregnant women as compared to the control group, also show significant decrease in high-density lipoprotein (HDL) level, SOD activity, and CAT activity in pregnant women as compared to nonpregnant women, and nonsignificant difference in uric acid, and HDL.